A principal manager's guide to leverage leadership 2.0 how to build exceptional schools across your district - Bambrick-Santoyo, Paul (a Wiley Brand, 2018)
Used in conjunction with Leverage Leadership 2.0, this book identifies the key actions principal managers should take to create exceptional school leaders, integrating the seven levers of leadership into district culture from the principal manager on up. With A Principal Manager's Guide to Leverage Leadership in hand, principal managers, superintendents and principal training organizations can facilitate district-wide and state-wide transformations and hasten the benefit to the students and community as a whole.